Bank Muamalat: a case in Islamic management - Mohd. Israil, Khaliq Ahmad; Kazmi, Azhar (Management Centre, IIUM, 2010)
In Malaysia, the promotion of the Islamic capital market sector overseas and in other Islamic markets, has been intensified, in particular through the sharing of Shariah knowledge in Islamic banking since the industry took off globally with the introduction of the Islamic Development Bank in Jeddah in 1970. In 1974, the Islamic Bank of Dubai became the first ever Islamic bank to be founded. The earliest form of Islamic banking in Malaysia can be traced to the setting up of the Perbadanan Wang Simpana Bakal-Bakal Haji, the precursor to the present-day Tabung Haji (TH). The National Steering Committee on Islamic Banks was established in July 1980 culminating in the establishment of Bank Islam Malaysia Berhad in 1983. In 1993, commercial banks, merchant banks and finance companies were allowed to offer Islamic banking products and services under the Islamic Banking Scheme (IBS). Bank Muamalat Malaysia Bhd took this opportunity to move into this industry and joined the existing Islamic banks in the country. Bank Muamalat is now one the leading banks in Malaysia. It has 46 branches, 5 service centres and an Labuan Offshore branch. At the time of data collection for this case study, the Bank had a staff strength of about 1,400 employees. Proficiency and integrity concerns are given serious thought and consideration due to increased level of competition in Islamic banking and finance in Malaysia with the opening of a number of international Islamic banks. A critical issue now is how the Bank develops and maintains its strategic position.